Placental Bioenergetics and Antioxidant Homeostasis in Maternal Obesity and Gestational Diabetes - Chiara Mandò; Sara Castiglioni; Chiara Novielli; Gaia Maria Anelli; Anaïs Serati; Francesca Parisi; Chiara Lubrano; Monica Zocchi; Roberta Ottria; Matteo Giovarelli (MDPI AG, 2024)
Maternal obesity has been associated with short- and long-term risks of pregnancy-perinatal adverse events, possibly due to alterations of placental mitochondrial bioenergetics. However, several detrimental mechanisms occurring in the placentas of women with obesity still need to be clarified. Here, we analyzed placental mitochondrial features and oxidative environment of 46 pregnancies in relation to pre-pregnancy BMI. Seventeen Caucasian normal-weight (NW) and twenty-nine women who were obese (OB) were enrolled. The protein expression of mitochondrial CypD and electron transfer chain complexes (C) I-V were measured, as well as ATP production and oxygen consumption rates (OCRs). The protein levels of the pro/anti-oxidant enzymes TXNIP, SOD2, and PON2 were also analyzed. Despite no differences in CypD expression, OCRs were significantly lower in OB vs. NW women. Accordingly, ATP synthase (CV) levels and ATP content were decreased in OB women, positively correlating with placental efficiency, suggesting a link between ATP deficiency and placental dysfunction. SOD2 expression negatively correlated with maternal BMI, indicating a possible impairment of antioxidant defenses with increasing BMI. These changes were worsened in 10 OB women presenting with gestational diabetes mellitus. Overall, these results suggest alterations of placental bioenergetics in pregnancies of women with obesity, possibly leading to placental dysfunction and altered fetal development and programming.